Proteome analysis of irradiated endothelial cells reveals persistent alteration in protein degradation and the RhoGDI and NO signalling pathways. (2nd September 2017) - Azimzadeh, Omid; Subramanian, Vikram; Ständer, Susanne; Merl-Pham, Juliane; Lowe, Donna; Barjaktarovic, Zarko; Moertl, Simone; Raj, Ken; Atkinson, Michael J.; Tapio, Soile
Abstract: Purpose: Epidemiological studies indicate that radiation doses as low as 0.5 Gy increase the risk of cardiovascular disease decades after the exposure. The aim of the present study was to investigate whether this radiation dose causes late molecular alterations in endothelial cells that could support the population-based data. Materials and methods: Human coronary artery endothelial cells were irradiated at 0.5 Gy (X-ray) and radiation-induced changes in the proteome were investigated after different time intervals (1, 7 and 14 d) using ICPL technology. Key changes identified by proteomics and bioinformatics were validated by immunoblotting and ELISA. Results: The radiation-induced alteration of the endothelial proteome was characterized by sustained perturbation of Rho GDP-dissociation inhibitor (RhoGDI) and nitric oxide (NO) signalling pathways. At later time-points, this was accompanied by reduced proteasome activity, enhanced protein carbonylation indicating augmented oxidative stress, and senescence. Conclusions: These molecular changes are indicative of long-term premature endothelial dysfunction and provide a mechanistic framework to the epidemiological data showing increased risk of cardiovascular disease at 0.5 Gy. Abstract :